Revision of the genus Dohrniphora Dahl (Diptera: Phoridae) from China - Liu, Guang-Chun (Zootaxa, 2015)
The Chinese species of Dohrniphora are revised, with 27 recognised species from both Oriental and Palaearctic China. The following 14 species are described as new to science: D. rectangularis sp. nov., D. capillais sp. nov., D. proxima sp. nov., D. longisetalis sp. nov., D. infrequens sp. nov., D. dentiretusa sp. nov., D. aspinula sp. nov., D. separata sp. nov., D. microtrichina sp. nov., D. dilatata sp. nov., D. disparilis sp. nov., D. carinata sp. nov., D. cespitula sp. nov., D. triangula sp. nov. D. microspinosa Shen & Liu, 2009 is regarded as a junior subjective synonym of D. prescherweberae Liu, 2001 and D. rectilinearis Liu, 2001 is a junior subjective synonym of D. malaysiae Green, 1997. Most known species were re-identified, re-described and illustrated. A revised key to Chinese male species is presented.